Designing 3d Animation For Dental Health Care Using Mdlc Method - Bayu Syahputra; Jimmy Pratama; vinson vinson (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
Dental health is one of the important aspect in being healthy because healthy teeth have a lot of purpose such as chewing food, words pronounciation and reduce risk of health problems. but even though it have such purposes netizen in indonesia still ignore it because the lack of health education not being taught since early age. Because of that, animation 3D become a choice for this research to educate people in the community about dental health care.The method for this research is qualitative interview and MDLC. The result from this research is an animation 3D about dental health care.